Decoding the Implicit Meanings: Analyzing Alan Walker’s ‘The Drum’ from a Social Semiotic Perspective - Sugiarto, Eko; Suardana, I Ketut; Astiari, Komang; Semadi, Yoga Putra (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research explores the application of social semiotics in analyzing the lyrics of Alan Walker's song "The Drum." Social semiotics examines how signs and symbols construct meaning within a social context. The research employs a qualitative approach, focusing on thematic analysis of the lyrics. The findings reveal that the song incorporates various social semiotic elements, including symbolism related to life's struggles, success, and the significance of guidance. The analysis suggests that "The Drum" can be interpreted as a motivational message about overcoming challenges and pursuing dreams. To realize the results and analysis of the songs, "The Drum" by Alan Walker's social semiotics into practice in the classroom, it needs to be done using various methods in various co-curricular activities (especially those integrating life skills) or through the habit of reading and singing or listening to beautiful songs of art, especially the works of young people who always have a very creative and constructive spirit.